Synthesis and Characterization of Novel Nano-,Micro- and Macroporous Lignin Sorbents for Purification of Biological Fluids - NN Chopabayeva; KN Mukanov (Journal of Chemical Engineering Research Updates, 2015)
Novel nano-, micro- and macroporous ion-exchangers based on hydrolytic lignin of cotton husk have been synthesized by two-step process including o-alkylation of biopolymer with diglycidyl ether of dioxydiphenylpropane and subsequent amination of formed glycidyl derivative. The optimal conditions of synthesis, composition, structure and physical, chemical properties of ion-exchangers were investigated by FTIR, SEM, porosimetry and potentiometric titration method. Textural characteristics of lignin and sorbents were also studied. It has been established that alkaline activated lignin shows an increase of SBET from 17.7 to 20.9 m2/g while modification leads to decrease of SBET more than double (from 14.5 to 9.2-5.2 m2/g) that of an untreared sample. Synthesized ion-exchangers are characterized by approximately identical porous structure and mainly contained a pore size of 10-14 nm. The results show the efficiency of lignin based sorbents for the removal of water and lipid soluble toxic metabolites from blood serum of diabetic retinopathy patients. Considerable detoxication effects of sorbents have potential for prevention and treatment of diabetes.